GAGASAN KURIKULUM SYARIAH MOCHAMAD SHOLEH Y.A.I DAN IMPLEMENTASINYA DI PERGURUAN MUHAMMADIYAH KOTTABARAT - Mohamad Ali; Hasniar Amanah (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2021)
This study aims to determine the ideas of Prof. Mochamad Sholeh Y.A.I, Ph.D related to the concept of the sharia curriculum and the implementation of the sharia curriculum at the Kottabarrat Muhammadiyah College. He is one of the figures who modified the curriculum, namely the sharia curriculum. Sharia curriculum development is planning inclusive learning that still leads to monotheism. This research is qualitative research with data obtained from the library (library search) and field research With a philosophical approach and descriptive analysis. The results show that the idea of the sharia curriculum of Prof. Mochamad Sholeh Y.A.I, Ph.D. is a modification of the national curriculum with five main elements, namely the Qur'an, al-Hadith, national curriculum, Indonesian nature, and International Development. The process of implementing the sharia curriculum at the Muhammadiyah Kottabarat Surakarta College is guided by the Sharia Science book which is used as a guide for teachers, students, and parents in the teaching process of students in such a way that intensive and inclusive interactions occur between children's learning processes at home, at school, and in the community. This inclusive-holistic learning process makes school institutions that excel in monotheism and science which in turn can create the ulul albab generation.